“Effects of the COVID-19 pandemic on university students’ physical health, mental health and learning, a cross-sectional study including 917 students from eight universities in Germany” - Gewalt, Sandra Claudia; Berger, Sarah; Krisam, Regina; Breuer, Markus (PLOS ONE, 2022)
The COVID-19 pandemic has severely affected physical and mental health. Since its commencement in 2020, social distancing has become the “new normal”. Temporary lockdowns and distance learning have disproportionately affected young adults, including university students. To identify effects of the pandemic on university students’ physical and mental health and learning, this empirical study included eight universities in Heidelberg, Mannheim and Ludwigshafen. Data was collected in May and June 2020. The self-administered survey was filled by 1,246 university students. 917 students completed the survey in full. 80.6% were bachelor students (n = 738), the mean semester was 3.8 and mean age was 23.1 years. 51.8% (n = 472) were female students and 47.4% (n = 432) male students. 38.5% (n = 352) stated a deterioration in physical health and 53.1% (n = 485) in mental health. From 0 to 10, students rated mean levels of stress highest due to social distancing (5.6), spending most time at home (5.0) and e-learning (4.5). Compared to male students, female students’ mental health worsened significantly (58.7% vs. 46.8%). A logistic regression analysis identified gender having a significant effect on university students’ stress levels: males seemed to have a lower risk of moderate to high levels of stress compared to females (odds ratio = 0.698; 95% CI = 0.515 to 0.945). Age, city of university and semester did not show a significant effect. The results are important to both regional and international audiences as university students face similar physical and mental health challenges due to the pandemic and its public health measures. Low-threshold initiatives are needed to mitigate the effects of the pandemic. These may include measures to reinforce students’ locus of control, sense of belonging, relaxation and mindfulness as well as (online) counselling services. Gender-specific differences must be taken into account.
Gesehen am 16.01.2023